Complex Post Traumatic Stress Disorder: A Review - Emre Han Alpay; Dilek Çelik (Psikiyatride Güncel Yaklaşımlar, 2022)
Complex trauma is a diagnosis that occurs due to repetitive, long-term and interpersonal traumatic events and its symptoms are different from post-traumatic stress disorder (PTSD). Although many studies have been conducted on complex trauma for many years, it has not been accepted as a different diagnosis. The 11th Edition of the International Classification of Diseases (ICD-11), published by the World Health Organization in 2018, includes complex post-traumatic stress disorder, a new diagnosis, besides post-traumatic stress disorder (PTSD) under the category of “Stress-Related Disorders”. In addition to the three diagnostic criteria of PTSD (re-experiencing, avoidance, and hypervigilance), 3 new symptoms related to self-organization have been added to this new diagnosis, namely emotion dysregulation, problems in interpersonal relationships, and negative self-concept. In this review study, firstly, the differences in the diagnosis of PTSD according to DSM-5 and ICD-11 were examined. Then, the history, definition and differences between complex PTSD disorder and other disorders were examined. Finally, studies on the methods used in the treatment of Complex PTSD were reviewed.